Earnings quality and trade credit in the Gulf Cooperation Council - Aws AlHares (17541741) (2023)
The primary concern of credit providers is the timely payment of obligations by clients, as most clients tend to pay their obligations late. To obtain accurate information from their buyers, credit providers need to rely on financial reporting or other information channels. The purpose of this study is to investigate the impact of earnings quality on trade credit, with a focus on the moderating role of accounting information comparability. We used Refinitiv Eikon and Fitch Connect databases to measure the variables. The study utilized financial information from 250 companies listed on the Gulf Cooperation Council (GCC), and six countries’ stock exchanges between 2016 and 2021 with 1500 firm-year observations. Panel data regression models were used to test the research hypotheses. This study aims to answer if earnings quality has an impact on trade credit and if the impact of earnings quality on trade credit is greater in companies with higher comparability than in companies with lower comparability. The findings revealed that earnings quality has a positive impact on trade credit. Moreover, the results suggested that an increase in accounting information comparability intensifies the effect of earnings quality on trade credit. This paper has repercussions for policymakers, investors, and business organizations. Importantly, our study reveals how higher levels of earnings quality lead to better trade credit practices. Other Information Published in: Journal of Governance and Regulation License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.22495/jgrv12i3art14